Exposed Subsoil Under Recovery for 30 Years: Influence of Management Strategies on Soil Physical Attributes and Organic Matter - Laura Silva Nantes; Carolina dos Santos Batista Bonini; Melissa Alexandre Santos; Lucas da Silva Alves; Josiane Lourencetti; Alfredo Bonini Neto; José Augusto Liberato de Souza; Gabriel Augusto da Silva Lunardelli; Mariana Bonini Silva; Dayara Vivian Alvares; Antonio Paz-Gonzalez (Soil Systems)
This study aimed to evaluate the residual effect of different management practices on a subsoil that has been exposed since 1969, which has been under recovery for 30 years. The soil under study is an Oxisol, and its assessment was conducted in 2023 and 2024. The experiment included nine treatments, with two controls, native vegetation and exposed soil, while the remaining treatments combined green manures (velvet bean, pigeon pea replaced by jack bean), liming, and liming + gypsum application from 1992 to 1997. Starting in 1999, Urochloa decumbens was planted in all plots, and from 2009, native Cerrado tree species naturally emerged. The following parameters were evaluated: gravimetric moisture, aggregate stability, infiltration rate, bulk density, soil penetration resistance, and organic matter content. Soil recovery management techniques reduced soil mechanical penetration resistance by 50% and soil density by 19.47%. The velvet bean increased gravimetric moisture by 11.32% compared to mobilized soil. The exposed soil exhibited an infiltration rate that was 90% lower than the other treatments. Conservation management practices increased the soil organic matter content, particularly in the 0–5 cm layer. Additionally, mucuna increased soil organic matter by 7% in the 10–20 cm layer and enhanced the soil organic carbon content. The strategies involving an initial use of velvet bean, velvet bean + liming, or velvet bean with liming + gypsum positively influenced the soil moisture, bulk density, aggregate stability, and organic matter at the 5–10 cm and 10–20 cm depths. Furthermore, the use of pigeon pea/jack bean with liming + gypsum improved attributes such as moisture, infiltration, and soil bulk density. It was concluded that green manuring enhances the physical properties of soil, with velvet bean or pigeon pea/jack bean combined with liming + gypsum being effective alternatives that are capable of positively impacting soil recovery.